Increasing Precision for Extended Reach 3D Manipulation - Auteri, Chris; Guerra, Mark; Frees, Scott (International Journal of Virtual Reality, 2013)
Object selection and manipulation in 3D immersive environments generally suffers from a lack of precision, primarily due to hand instability and tracking noise. Typically the lack of precision is exacerbated as the user begins to use techniques that allow distant interaction, such as Ray Casting, HOMER, and Go-Go. This problem can be addressed using velocity-based hand scaling such as PRISM, which has been applied to Ray Casting and HOMER previously. We present a study of the combination of Go-Go and PRISM. In our research, we have found that Go-Go + PRISM yields a nearly 2:1 improvement in precision over traditional Go-Go interaction when attempting to align two objects at a distance under time constraints